Method for evaluating influence of underground water matrix on electron transfer in TMAC / PAA system based on electrochemical means

The impact of groundwater matrix on carbon material activation PAA system was evaluated through electrochemical means, and the problem of unstable organic pollutant removal efficiency in groundwater was solved, and efficient treatment of groundwater and industrial wastewater was achieved.

CN119246650APending Publication Date: 2025-01-03TONGJI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411506118.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The prior art lacks direct and efficient methods to evaluate the impact of groundwater matrix on electron transfer process in carbon material activation PAA system, resulting in unstable organic pollutant removal efficiency in groundwater.

Method used

Using an electrochemical method, using a foam nickel and platinum electrode of a loaded thermally modified activated carbon material, combined with sodium sulfate electrolyte, sample solution and PAA solution were added, and the electron transfer process was monitored by open circuit voltage method and linear scanning voltammetry to evaluate the The influence of groundwater matrix on TMAC/PAA system.

Benefits of technology

This method can directly and accurately monitor the impact of groundwater matrix on electron transfer in carbon material activated PAA system, reduce secondary pollution, low cost, and is suitable for groundwater and industrial wastewater treatment, with wide application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119246650A_ABST
    Figure CN119246650A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of underground water pollution treatment, and discloses a method for evaluating the influence of an underground water matrix on electron transfer in a TMAC / PAA system based on an electrochemical means. The method comprises the following steps: taking foamed nickel loaded with a thermal modified activated carbon material and a platinum electrode as working electrodes, taking sodium sulfate as an electrolyte, adding a sample solution, connecting an electrochemical workstation, adding a PAA solution and an SMX stock solution, monitoring electron transfer in a reaction process, and verifying the influence of a matrix in the sample solution on TMAC-PAA * by adopting an open-circuit voltage method, verifying the influence of the matrix in the sample solution on electron transfer in the TMAC / PAA system by adopting linear scanning voltammetry; the matrix comprises pH, anions and humic acid. The method provided by the invention has high sensitivity and accuracy, can monitor and record key parameters in the electron transfer process in real time, and provides accurate data support for evaluating the influence of an underground water matrix on the electron transfer process in the carbon material activated PAA system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of groundwater pollution control, and in particular to a method for evaluating the influence of groundwater matrix on electron transfer in a TMAC / PAA system based on electrochemical means. Background Art

[0002] Groundwater pollution is one of the important issues in the current field of environmental protection, among which the removal of organic pollutants is particularly critical.

[0003] Sulfamethoxazole (SMX) is a typical active pharmaceutical compound that can easily enter the groundwater system directly or indirectly through human production activities. It is also difficult to degrade and has high persistence in water bodies. In recent years, advanced oxidation technology has attracted much attention and is considered to be an effective means of treating SMX, but traditional advanced oxidation technology still cannot effectively degrade SMX.

[0004] Peracetic acid (PAA), as a strong oxidant, has high selectivity for the removal of different organic matter, and has the advantages of easy activation, wide pH range, and less toxic byproducts. It has unique advantages and broad application prospects in the removal of new pollutants in groundwater. Carbonaceous materials have the advantages of high specific surface area, rich functional groups, and easy modification. In recent years, they have gradually become an emerging catalyst for activating PAA to degrade organic micropollutants in groundwater.

[0005] In addition, carbon materials have low production costs, good structural stability and reusability, and can avoid the high energy consumption of ultraviolet activation and secondary pollution problems such as metal activation. Due to the poor surface stability of unmodified carbonaceous material catalysts, carbonaceous material catalysts under the same material show differences in catalytic performance. However, the groundwater matrix is ​​complex and changeable, which has a significant impact on the activation effect of PAA and the electron transfer process.

[0006] In the prior art, there is a lack of a method for directly and efficiently evaluating the effect of groundwater matrix on the electron transfer process in the PAA system activated by carbon materials. The present invention provides an electrochemical method for evaluating the effect of groundwater matrix on the electron transfer process in the PAA system activated by carbon materials. Summary of the invention

[0007] The purpose of the present invention is: based on the above technical problems, the present invention provides a method for evaluating the influence of groundwater matrix on electron transfer in TMAC / PAA system based on electrochemical means.

[0008] In order to achieve the above object, the first aspect of the present invention provides a method for evaluating the effect of groundwater matrix on electron transfer in TMAC / PAA system based on electrochemical means, the method comprising the following steps:

[0009] Using nickel foam and platinum electrodes loaded with thermally modified activated carbon materials as working electrodes and sodium sulfate as electrolyte, adding sample solution, connecting to an electrochemical workstation, adding PAA solution and SMX stock solution, monitoring electron transfer during the reaction, and using open circuit voltage method to verify the effect of the matrix in the sample solution on TMAC-PAA*, and then using linear sweep voltammetry to verify the effect of the matrix in the sample solution on electron transfer in the TMAC / PAA system;

[0010] The matrix includes pH, anions, and humic acid.

[0011] Preferably, the thermally modified activated carbon material is TMAC.

[0012] According to a particularly preferred embodiment, the nickel foam loaded with thermally modified activated carbon material is obtained by a method comprising the following steps:

[0013] S1: Add nickel foam of size 1mm×10mm×20mm into 10wt% baking soda solution, boil for 30min to remove grease on the surface of nickel foam, immerse in 6.0mol / L hydrochloric acid, ultrasonically treat for 10min to remove the oxide layer on the surface of nickel foam, take out, immerse in deionized water, ultrasonically treat for 20min, and wash with acetone;

[0014] S2: Disperse 1-100 mg TMAC in 10-500 μL isopropyl ketone, ultrasonically treat for 15 min, then add 10-500 μL 5 wt% perfluorinated resin, and ultrasonically treat for 25 min to obtain a catalyst slurry;

[0015] S3: evenly apply the catalyst slurry on the surface of the nickel foam obtained in step S1, put it into an oven to dry for 18 hours, and then set aside.

[0016] Preferably, the pH value of the sample solution ranges from 3 to 11.

[0017] Preferably, the pH is adjusted using a NaOH solution with a concentration of 0.1 mmol / L or a HNO3 solution with a concentration of 0.1 mmol / L.

[0018] Further preferably, the sample solution contains Cl - and HCO3 - .

[0019] Preferably, the sample solution contains humic acid at a concentration of 0 to 50 mg / L.

[0020] Preferably, the PAA solution is added so that the concentration of the PAA solution in the mixed solution is 0.26 mmol / L.

[0021] Preferably, SMX stock solution is added so that the concentration of the SMX stock solution in the mixed solution is 20 mg / L.

[0022] More preferably, the PAA solution is added at 150s or 200s from the time when the electrochemical workstation is connected.

[0023] Preferably, the SMX stock solution is added at 700s or 1500s from the time the electrochemical workstation is connected.

[0024] The method provided by the present invention has at least the following beneficial effects:

[0025] (1) The method provided by the present invention can directly observe the influence of groundwater matrix on the electron transfer process in the carbon material activation PAA system through electrochemical means, which helps to reveal the differences in PAA activation efficiency under different water quality conditions.

[0026] (2) The method provided by the present invention does not require the addition of a large amount of chemical substances, thus reducing secondary pollution, having low treatment costs and being environmentally friendly.

[0027] (3) The method provided by the present invention has high sensitivity and accuracy, and can monitor and record the key parameters in the electron transfer process in real time, providing accurate data support for evaluating the influence of groundwater matrix on the electron transfer process in the carbon material activated PAA system.

[0028] (4) The method provided by the present invention is not only applicable to the degradation treatment process of organic pollutants in groundwater environment, but can also be extended to fields such as industrial wastewater treatment, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a linear scanning curve diagram measured under the condition of pH 3 to 11 of the present invention;

[0030] Figure 2 The present invention is Cl - Linear scan curve graph measured in the presence of;

[0031] Figure 3 The present invention is in HCO3 - Linear scan curve graph measured in the presence of;

[0032] Figure 4 It is a linear scanning curve diagram measured at different humic acid concentrations of the present invention;

[0033] Figure 5 It is a linear scanning curve diagram measured by the present invention using real groundwater. DETAILED DESCRIPTION

[0034] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0035] In the present invention, the open circuit potential method and the linear sweep voltammetry method are both existing disclosed methods.

[0036] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, the raw materials are all commercially available.

[0037] In the following examples, unless otherwise specified, TMAC refers to thermally modified activated carbon.

[0038] In the following examples, unless otherwise specified, humic acid was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0039] Preparation Example

[0040] This example is used to provide a method for preparing a nickel foam loaded with TMAC, the method comprising the following steps:

[0041] S1: Add nickel foam of size 1mm×10mm×20mm into 10wt% baking soda solution, boil for 30min to remove grease on the surface of nickel foam, immerse in 6.0mol / L hydrochloric acid, ultrasonically treat for 10min to remove the oxide layer on the surface of nickel foam, take out, immerse in deionized water, ultrasonically treat for 20min, and wash with acetone;

[0042] S2: Disperse 1-100 mg TMAC in 10-500 μL isopropyl ketone, ultrasonically treat for 15 min, then add 10-500 μL 5 wt% perfluorinated resin, and ultrasonically treat for 25 min to obtain a catalyst slurry;

[0043] S3: evenly apply the catalyst slurry on the surface of the nickel foam obtained in step S1, put it into an oven to dry for 18 hours, and then set aside.

[0044] Example 1

[0045] This example is used to provide an electrochemical method to evaluate the effect of pH on electron transfer in the TMAC / PAA system. The method includes:

[0046] Using nickel foam and platinum electrodes loaded with TMAC as working electrodes and sodium sulfate as electrolyte, the initial pH of the mixed solution was adjusted to 3 with 0.1mmol / L NaOH solution and 0.1mmol / L HNO3 solution in 20mL ultrapure water, and the experiment was started. The timing started from the connection of the electrochemical workstation. At 150s, PAA solution was added to make the concentration of PAA solution in the mixed solution 0.26mmol / L. At 1500s, SMX stock solution was added to make the concentration of SMX stock solution in the mixed solution 20mg / L. The electrochemical workstation was connected, and the open circuit potential method was used to verify the effect of pH on TMAC-PAA* during the activation of PAA by TMAC and the degradation of SMX.

[0047] The nickel foam and platinum electrodes loaded with TMAC were used as working electrodes, sodium sulfate was used as the electrolyte, and 20 mL of 20 mg / L SMX stock solution was added. The initial pH of the mixed solution was adjusted to 3 with 0.1 mmol / L NaOH solution and 0.1 mmol / L HNO3 solution. PAA solution was quickly added to make the concentration of PAA solution in the mixed solution 0.26 mmol / L. Linear sweep voltammetry was used to verify the effect of pH on the electron transfer process during the activation of PAA by TMAC and the degradation of SMX.

[0048] Example 2

[0049] The method of Example 1 was followed, except that the initial pH of the mixed solution was adjusted to 5, and the remaining steps and parameters were the same as those of Example 1.

[0050] Example 3

[0051] The method of Example 1 was followed, except that the initial pH of the mixed solution was adjusted to 7, and the remaining steps and parameters were the same as those of Example 1.

[0052] Example 4

[0053] The method of Example 1 was followed, except that the initial pH of the mixed solution was adjusted to 9, and the remaining steps and parameters were the same as those of Example 1.

[0054] Example 5

[0055] The method of Example 1 was followed, except that the initial pH of the mixed solution was adjusted to 11, and the remaining steps and parameters were the same as those of Example 1.

[0056] Example 6

[0057] This example is used to provide an electrochemical method to evaluate Cl - 、HCO3 - The effect on electron transfer in the TMAC / PAA system, the method comprising:

[0058] The nickel foam and platinum electrodes loaded with TMAC were used as working electrodes, sodium sulfate was used as electrolyte, 20 mL of ultrapure water was added, NaCl was added thereto, so that the concentration of NaCl in the electrolyte was 50 mmol / L, and NaHCO3 was added thereto, so that the concentration of NaHCO3 in the electrolyte was 300 mg / L. The experiment was started, and the timing was started from the connection of the electrochemical workstation. PAA solution was added at 200 s, so that the concentration of PAA solution in the mixed solution was 0.26 mmol / L. At 700 s, SMX stock solution was added, so that the concentration of SMX stock solution in the mixed solution was 20 mg / L. The electrochemical workstation was connected, and the open circuit potential method was used to verify that Cl - 、HCO3 - Effects on TMAC-PAA*.

[0059] The nickel foam and platinum electrodes loaded with TMAC were used as working electrodes, sodium sulfate was used as electrolyte, 20 mL of 20 mg / L SMX stock solution was added, NaCl was added thereto so that the concentration of NaCl in the mixed solution was 50 mmol / L, and then NaHCO3 was added thereto so that the concentration of NaHCO3 in the mixed solution was 300 mg / L, and then PAA solution was quickly added so that the concentration of PAA solution in the mixed solution was 0.26 mmol / L. The electrochemical workstation was connected, and linear sweep voltammetry was used to verify that during the activation of PAA by TMAC and the degradation of SMX, Cl - 、HCO3 - The effect on the electron transfer process.

[0060] Example 7

[0061] The method of Example 6 is followed, except that NaCl is added thereto so that the concentration of NaCl in the electrolyte is 10 mmol / L, and NaHCO3 is then added thereto so that the concentration of NaHCO3 in the electrolyte is 150 mg / L. The remaining steps and parameters are the same as those of Example 6.

[0062] Example 8

[0063] The method of Example 6 is followed, except that NaCl is added thereto so that the concentration of NaCl in the electrolyte is 5 mmol / L, and NaHCO3 is then added thereto so that the concentration of NaHCO3 in the electrolyte is 100 mg / L. The remaining steps and parameters are the same as those of Example 6.

[0064] Example 9

[0065] The method of Example 6 is followed, except that NaCl is added thereto so that the concentration of NaCl in the electrolyte is 1 mmol / L, and NaHCO3 is then added thereto so that the concentration of NaHCO3 in the electrolyte is 50 mg / L. The remaining steps and parameters are the same as those of Example 6.

[0066] Example 10

[0067] The method of Example 6 is followed, except that NaCl is added thereto so that the concentration of NaCl in the electrolyte is 0 mmol / L, and then NaHCO3 is added thereto so that the concentration of NaHCO3 in the electrolyte is 0 mg / L. The remaining steps and parameters are the same as those of Example 6.

[0068] Embodiment 11

[0069] This example is used to provide an electrochemical method to evaluate the effect of humic acid on electron transfer in the TMAC / PAA system. The method includes:

[0070] The nickel foam and platinum electrodes loaded with TMAC were used as working electrodes, sodium sulfate was used as electrolyte, 20 mL of ultrapure water was added, humic acid was added thereto, so that the concentration of humic acid in the electrolyte was 50 mg / L, the experiment was started, and the timing was started from the connection of the electrochemical workstation. At 150 seconds, the PAA solution was added, so that the concentration of the PAA solution in the mixed solution was 0.26 mmol / L, and at 700 seconds, the SMX stock solution was added, so that the concentration of the SMX stock solution in the mixed solution was 20 mg / L. The electrochemical workstation was connected, and the open circuit potential method was used to verify the effect of humic acid on TMAC-PAA* during the activation of PAA by TMAC and the degradation of SMX.

[0071] Using TMAC-loaded nickel foam and platinum electrodes as working electrodes and sodium sulfate as electrolyte, 20 mL of 20 mg / L SMX stock solution was added, and humic acid was added thereto so that the concentration of humic acid in the electrolyte was 50 mg / L. Then, PAA solution was quickly added so that the concentration of PAA solution in the mixed solution was 0.26 mmol / L. An electrochemical workstation was connected, and linear sweep voltammetry was used to verify the effect of humic acid on the electron transfer process during the activation of PAA by TMAC and the degradation of SMX.

[0072] Example 12

[0073] The method of Example 11 is followed, except that humic acid is added thereto so that the concentration of humic acid in the electrolyte is 10 mg / L. The remaining steps and parameters are the same as those of Example 11.

[0074] Embodiment 13

[0075] The method of Example 11 is followed, except that humic acid is added thereto so that the concentration of humic acid in the electrolyte is 5 mg / L. The remaining steps and parameters are the same as those of Example 11.

[0076] Embodiment 14

[0077] The method of Example 11 is followed, except that humic acid is added thereto so that the concentration of humic acid in the electrolyte is 1 mg / L. The remaining steps and parameters are the same as those of Example 11.

[0078] Embodiment 15

[0079] The method of Example 11 is followed, except that humic acid is added thereto so that the concentration of humic acid in the electrolyte is 0 mg / L. The remaining steps and parameters are the same as those of Example 11.

[0080] Example 16

[0081] This example is used to provide an electrochemical method to evaluate the effect of real groundwater samples on electron transfer in the TMAC / PAA system. The method includes:

[0082] The nickel foam and platinum electrodes loaded with TMAC were used as working electrodes, sodium sulfate was used as electrolyte, 100 mL of real groundwater sample was added, the experiment was started, and the timing started from the connection of the electrochemical workstation. PAA solution was added at 200 seconds to make the concentration of PAA solution in the mixed solution 0.26 mmol / L. At 500 seconds, SMX stock solution was added to make the concentration of SMX stock solution in the mixed solution 20 mg / L. The electrochemical workstation was connected, and the open circuit potential method was used to verify the effect of TMAC-PAA* in the process of TMAC activation of PAA and degradation of SMX.

[0083] Using TMAC-loaded nickel foam and platinum electrodes as working electrodes and sodium sulfate as electrolyte, SMX stock solution diluted to a concentration of 20 mg / L with real groundwater samples was added, and PAA solution was quickly added to make the concentration of PAA solution in the mixed solution 0.26 mmol / L. The electrochemical workstation was connected, and linear sweep voltammetry was used to verify the effect of TMAC on the electron transfer process during the activation of PAA and the degradation of SMX.

[0084] Embodiment 17

[0085] The method of Example 16 was followed, except that the same amount of ultrapure water was used to replace the real groundwater sample, and the remaining steps and parameters were the same as Example 16.

[0086] Test Example 1

[0087] Summarize the test results of the electrochemical methods in Examples 1 to 5 above. The results are as Figure 1 shown.

[0088] It can be seen from Figure 1 that when using linear sweep voltammetry for testing, at different initial pH values, there are significant differences in the current generated by the degradation of SMX in the TMAC / PAA system. When the applied potential is 1 V, the order of the current magnitude is pH = 3 (2.406 mA) < pH = 11 (3.687 mA) < pH = 5 (3.793 mA) < pH = 9 (3.922 mA) < pH = 7 (7.227 mA). The results show that in the TMAC / PAA system, the electron transfer intensity of SMX is inhibited to varying degrees in strongly acidic or alkaline environments, and stronger currents are obtained under weakly acidic, alkaline, and neutral conditions.

[0089] Test Example 2

[0090] Summarize the test results of the electrochemical methods in Examples 6 to 10 above. The results are as Figure 2 and Figure 3 shown.

[0091] It can be seen from Figure 2 and Figure 3 that in the presence of anions at appropriate concentrations, the efficiency of electron transfer is improved. It can be seen that Cl - can improve the electron transfer efficiency, while HCO3 - has strong Lewis basicity and is prone to inducing the H + (Lewis acid) ionized from PAA in water to conduct electron transfer, consuming PAA in water and inhibiting the formation of TMAC-PAA*.

[0092] Test Example 3

[0093] Summarize the test results of the electrochemical methods in Examples 11 to 15 above. The results are as Figure 4 shown.

[0094] It can be seen from Figure 4 that the peak current observed at a humic acid concentration of 0 mg / L is not much different from that of the groups with humic acid concentrations of 1, 5, and 10 mg / L. However, when the humic acid concentration rises to 50 mg / L, the oxidation current decays sharply. As the humic acid concentration increases, the maximum current difference goes through a process of first increasing and then decreasing. This result indicates that high concentrations of humic acid will lead to a decrease in the oxidation reaction rate in the TMAC / PAA system and hinder the electron transfer efficiency. However, under the stimulation of humic acid at a concentration of 1 to 30 mg / L, the TMAC / PAA system can improve the electron transfer efficiency.

[0095] Test Example 4

[0096] Summarizing the electrochemical test results of Examples 16 to 17, the results are as follows: Figure 5 shown.

[0097] Depend on Figure 5 It can be seen that in the complex groundwater matrix, the electron transfer pathway still maintains normal operation, and the TMACI / PAA system can still maintain a good degradation effect on SMX in the real groundwater environment.

[0098] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for evaluating the effect of groundwater matrix on electron transfer in TMAC / PAA system based on electrochemical means, characterized in that: The method comprises the following steps: Using nickel foam and platinum electrodes loaded with thermally modified activated carbon materials as working electrodes and sodium sulfate as electrolyte, adding sample solution, connecting to an electrochemical workstation, adding PAA solution and SMX stock solution, monitoring electron transfer during the reaction, and using open circuit voltage method to verify the effect of the matrix in the sample solution on TMAC-PAA*, and then using linear sweep voltammetry to verify the effect of the matrix in the sample solution on electron transfer in the TMAC / PAA system; The matrix includes pH, anions, and humic acid.

2. The method according to claim 1, wherein: The thermally modified activated carbon material is TMAC.

3. The method according to claim 1 or 2, wherein: The nickel foam loaded with thermally modified activated carbon material is obtained by a method comprising the following steps: S1: Add nickel foam of size 1mm×10mm×20mm into 10wt% baking soda solution, boil for 30min to remove grease on the surface of nickel foam, immerse in 6.0mol / L hydrochloric acid, ultrasonically treat for 10min to remove the oxide layer on the surface of nickel foam, take out, immerse in deionized water, ultrasonically treat for 20min, and wash with acetone; S2: Disperse 1-100 mg TMAC in 10-500 μL isopropyl ketone, ultrasonically treat for 15 min, then add 10-500 μL 5 wt% perfluorinated resin, and ultrasonically treat for 25 min to obtain a catalyst slurry; S3: evenly apply the catalyst slurry on the surface of the nickel foam obtained in step S1, put it into an oven to dry for 18 hours, and then set aside.

4. The method according to claim 1 or 2, wherein: The pH value of the sample solution ranges from 3 to 11; And / or, a NaOH solution with a concentration of 0.1 mmol / L or a HNO3 solution with a concentration of 0.1 mmol / L is used to adjust the pH.

5. The method according to claim 1 or 2, wherein: The sample solution contains Cl - and HCO3 - .

6. The method according to claim 1 or 2, wherein: The sample solution contains humic acid at a concentration of 0 to 50 mg / L.

7. The method according to claim 1 or 2, wherein: The PAA solution was added to make the concentration of the PAA solution in the mixed solution be 0.26 mmol / L.

8. The method according to claim 1 or 2, wherein: SMX stock solution was added so that the concentration of the SMX stock solution in the mixed solution was 20 mg / L.

9. The method according to claim 1 or 2, wherein: Start timing from the time the electrochemical workstation is connected, and add the PAA solution at 150s or 200s.

10. The method according to claim 1 or 2, wherein: Start timing from the time the electrochemical workstation is connected, and add SMX stock solution at 700s or 1500s.